Numerical Determination of Effects of Wall Temperatures on Nusselt Number and Convective Heat Transfer Coefficient in Real-Size Rooms - Acikgoz, Ozgen; Kincay, Olcay (SAGE PUBLICATIONS LTD, 2013)
A modeled room was numerically heated from a wall and cooled from the opposite wall in order to create a real-room simulation. The cooled wall simulated heat loss of the room, and the heated wall simulated the heat source of enclosure. The effects of heated and cooled wall temperatures on convective heat transfer coefficient (CHTC) and Nusselt number in the enclosure were investigated numerically for two-(2D) and three-dimensional (3D) modeling states. Different hot wall and cold wall temperatures were applied in order to obtain correlations that contained characteristic length in Rayleigh numbers. Results were compared with the results of previously reported correlations that have been suggested for vertical room surfaces in enclosures. In addition, new correlations for Nusselt number and average CHTC for enclosures for isothermal boundary conditions within indicated Rayleigh number ranges were derived through solutions. Average deviations of new correlations obtained for CHTC and Nusselt number from the numerical data were found 0.73% and 1.76% for 2D study, 3.01% and 0.49% for 3D study. It was observed that the difference between the 2D and 3D solutions in terms of CHTC and Nusselt number was approximately 10%.
Keywords: NATURAL-CONVECTION; SURFACES; Thermodynamics; Engineering